SOX9 predicts progression toward cirrhosis in patients while its loss protects against liver fibrosis. Issue 12 (6th November 2017) - Athwal, Varinder S; Pritchett, James; Llewellyn, Jessica; Martin, Katherine; Camacho, Elizabeth; Raza, Sayyid MA; Phythian‐Adams, Alexander; Birchall, Lindsay J; Mullan, Aoibheann F; Su, Kim; Pearmain, Laurence; Dolman, Grace; et al.
Abstract: Fibrosis and organ failure is a common endpoint for many chronic liver diseases. Much is known about the upstream inflammatory mechanisms provoking fibrosis and downstream potential for tissue remodeling. However, less is known about the transcriptional regulation in vivo governing fibrotic matrix deposition by liver myofibroblasts. This gap in understanding has hampered molecular predictions of disease severity and clinical progression and restricted targets for antifibrotic drug development. In this study, we show the prevalence of SOX9 in biopsies from patients with chronic liver disease correlated with fibrosis severity and accurately predicted disease progression toward cirrhosis. Inactivation of Sox9 in mice protected against both parenchymal and biliary fibrosis, and improved liver function and ameliorated chronic inflammation. SOX9 was downstream of mechanosignaling factor, YAP1. These data demonstrate a role for SOX9 in liver fibrosis and open the way for the transcription factor and its dependent pathways as new diagnostic, prognostic, and therapeutic targets in patients with liver fibrosis. Synopsis: The extent of SOX9 detection in liver correlates with the severity of fibrosis and predicts its progression toward cirrhosis in patients with chronic liver disease. In mice, SOX9 loss improves scarring and ameliorates liver function and inflammation. Mechanosensitive signaling regulates SOX9 via YAP1; SOX9 regulates multiple components of the ECM in liver myofibroblasts. In rodent models of liver fibrosis Sox9 loss reduced scarring, improved liver function and blocked macrophage maturation resulting in fewer F4/80‐positive macrophages. In patients, the profile of SOX9 detection following liver injury was identical to that observed in mouse. Prevalence of SOX9 expression in biopsies from patients with chronic liver disease correlated precisely with fibrosis severity. The extent of SOX9 in patients with early stages of liver disease predicted progression within 3 years and performed better than other associated fibrosis risk factors. Abstract : The extent of SOX9 detection in liver correlates with the severity of fibrosis and predicts its progression toward cirrhosis in patients with chronic liver disease. In mice, SOX9 loss improves scarring and ameliorates liver function and inflammation.